Patients satisfaction with healthcare delivery in Ghana - Amporfro, Daniel Adjei (BMC Health Serv Res, 2021)
BACKGROUND: The service industry has been an evolving sector and a great concern to providers ensuring continuously that clients’ satisfaction is met. Hence, the importance of patient satisfaction in the healthcare sector. This study focused on the satisfaction of women with the delivery of health services in Ghana and aims to be different from other studies which has focused on patient satisfaction with urban and rural health services, regional health services and health insurance. Our study examines the percentages of satisfaction with the multiple outcomes defined and identifies the key health system and demographic related factors associated with women satisfaction. METHODS: This study used data from the 2014 Ghana Demographic and Health Survey and a total of 12,831 households were systematically selected with reproductive women aged 15–49 years eligible for interview. Data for this study was analysed quantitatively using descriptive statistics, chi square and regression analysis. A total of 3648 women were included in this study and the final analysis thus involved a weighted sample of 3507 women. Satisfaction indicators were put together into SERVQUAL dimensions in the study and reliability test run using Cronbach Alpha (α). All data analyses were carried out in STATA 13.0. The adjusted odds ratios (AOR) with their corresponding 95% confidence intervals (CI) were calculated. RESULTS: Analysis showed that independently, education and religion were significantly associated with service reliability, overall satisfaction and responsiveness. Payment option was also associated with responsiveness and tangibility dimensions. Furthermore, place of residence was independently associated with responsiveness, tangibility and overall satisfaction. Finally, maternal age, region, provider friendly, ease of getting care and opening hours were all independently associated with reliability, responsiveness, tangibility and overall service satisfaction at the multivariable level. CONCLUSIONS: Dimensions of service quality which focus on patient-centered atmosphere and efficient service delivery system should be integrated and strengthened by hospital management in order to increase patient satisfaction. Key maternal characteristics and health system related factors were revealed to have positive association with patient satisfaction with health services delivery and this cannot be ignored by health care managers in ensuring that systems are improved for better health care.